Gerak Lurus Berbasis Arduino Uno: Alat Peraga Fisika Alternatif menggunakan Linear Air Track - Istiqomah Istiqomah; Yusro Al Hakim; Eko Satyadi Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2020)
Alternative physics teaching aid with linear air track based on Arduino Uno have been developed to determine: (1) the accuracy of the teaching aid (2) the validity of the teaching aid, and (3) the practicality of the teaching aid. This research was conducted in the Physics Education study program, Muhammadiyah University of Purworejo. This research adapts the ADDIE (Analysis Design Develop Implement Evaluation) development model. The analysis technique uses a trial analysis tool, validation instrument data, student response questionnaire data and the implementation of learning and experimental results. Based on the trial of the tool carried out by calculating the time manually and using a sensor, the difference in mean value is 0.008 s. Based on the analysis of the validation results, it was obtained an average score of 3.14 with a percentage of 86.33% (very good category). The results of the analysis of the implementation of learning in the preliminary aspects obtained a mean value of 16.00, the core activity aspects were 26.00 and the closing aspects were 16.00. These three aspects obtained an average score of 3.75 in the very good category. Based on this analysis, it can be concluded that this development research produces learning media in the form of teaching aid for straight motion with a linear air track based on Arduino Uno to calculate the time of objects as they pass with good accuracy and validity and practical teaching aid used for learning.